Metabolome and transcriptome analysis on muscle of sporadic inclusion body myositis. Issue 10 (15th September 2022) - Murakami, Ayuka; Noda, Seiya; Kazuta, Tomoyuki; Hirano, Satoko; Kimura, Seigo; Nakanishi, Hirotaka; Matsuo, Koji; Tsujikawa, Koyo; Iida, Madoka; Koike, Haruki; Sakamoto, Kazuma; Hara, Yuichiro; et al.
Abstract: Objective: Sporadic inclusion body myositis (sIBM) is the most common acquired myopathy in patients older than 50 years of age. sIBM is hardly responds to any immunosuppressing theraphies, and its pathophysiology remains elusive. This study aims to explore pathogenic pathways underlying sIBM and identify novel therapeutic targets using metabolomic and transcriptomic analyses. Methods: In this retrospective observational study, we analyzed biopsied muscle samples from 14 sIBM patients and six non‐diseased subjects to identify metabolic profiles. Frozen muscle samples were used to measure metabolites with cation and anion modes of capillary electrophoresis time of flight mass spectrometry. We validated the metabolic pathway altered in muscles of sIBM patients through RNA sequencing and histopathological studies. Results: A total of 198 metabolites were identified. Metabolomic and transcriptomic analyses identified specific metabolite changes in sIBM muscle samples. The pathways of histamine biosynthesis and certain glycosaminoglycan biosynthesis were upregulated in sIBM patients, whereas those of carnitine metabolism and creatine metabolism were downregulated. Histopathological examination showed infiltration of mast cells and deposition of chondroitin sulfate in skeletal muscle samples, supporting the results of metabolomic and transcriptomic analyses. Interpretation: We identified alterations of several metabolic pathways in muscle samples of sIBM patients. These results suggest that mast cells, chondroitin sulfate biosynthesis, carnitine, and creatine play roles in sIBM pathophysiology.